(3JShjb GdNOeGJ GdUMjIs - (3KGeQ jGSQ(B, (3GdHcQjs ((3YeGf(B:s (3OGQ GdjGRhQj(B,s, 2005)
(3GdaUd GdChd (B: (3NdajI YGeI ai GdJShjb hGdNOeGJ GdJShjbjI (B: (3GdebOeI (B: (3eaghe GdJShjb (B: (3GdNOeGJ GdJShjbjI (B: (3eaghe GdNOeGJ GdJShjbi (B: (3NUGFU GdNOeGJ GdJShjbjI(B-(3GdaUd GdKGfi (B: (3GdJShjb GdUMi (B/ (3Gdeaghe(B, (3GdJWhQ(B, (3GdCgejI(B, (3hGdNUGFU(B: (3GdebOeI (B: (3eaghe GdJShjb GdUMi (B: (3GdJWhQ GdacQi ddJShjb GdUMi (B: (3GdJhLg fMh GdEfJGL (B: (3GdJhLg fMh GdefJL (B: (3GdJhLg fMh GdeHjYGJ (B: (3GdJhLg GdJShjbi (B: (3GdJhLg GdGLJeGYi ddJShjb (B: (3GdeOGNd ai GdeSDdjI GdGLJeGYjI (B: (3MGLI GdeSJTajGJ ddJShjb(B-(3GdaUd GdKGdK (B: (3JMdjd Sdhc GdeSJgGc (B: (3GdebOeI (B: (3GdeSJgdc hGdSdhc GdTQGFi (B: (3GdYhGed GdeDKQI ai GdSdhc GdTQGFi ddeSJgdc (B: (3GdYhGed GdKbGajI (B: (3GdYhGed GdGLJeGYjI (B: (3GdYhGed GdTNUjI (B: (3GdYhGed GdfaSjI (B: (3eQGMd TQGA GdNOeI GdUMjI (B: (3MGLI GdeQVi hSdhcge(B-(3GdaUd GdQGHY (B: (3fXe GdYdheGJ GdJShjbjI (B: (3GdebOeI (B: (3JYQja hCgejI fXGe GdeYdheGJ GdJShjbi (B: (3BdjI Yed fXGe GdeYdheGJ GdJShjbi (B: (3echfGJ fXGe GdeYdheGJ GdJShjbi GdUMi(B-(3GdaUd GdNGeS (B: (3GdJNWjW GdJShjbi ai GdeSJTai (B: (3GdebOeI (B: (3GdJNWjW GdJShjbi hGdeRGjG GdeJMbbI efg (B: (3GdCHYGO GdRefjI ddJNWjW GdJShjbi (B: (3eVGejf GdJNWjW GdGSJQGJjLi GdUMi(B-(3GdaUd GdSGOS (B: (3GdebOeI (B: (3JLRFI GdShb GdUMi hGNJjGQ GdShb GdeSJgdc (B: (3eaghe JLRFI GdShb GdUMi(B-(3GdaUd GdSGHY (B: (3GdebOeI (B: (3GdefJL (B((3GdNOeI(B) (3ai GdeSJTai (B: (3GdCgejI GdJShjbjI defJL GdeSJTai(B-(3GdaUd GdKGef (B: (3GdfhYjI ai GdNOeI GdUMjI (B: (3GdebOeI (B: (3JYQja GdfhYjI ai GdNOeI GdUMjI (B: (3CgejI GdfhYjI ai GdNOeI GdUMjI(B-(3GdaUd GdJGSY (B: (3GdJQhjL GdUMi (B: (3GdebOeI (B: (3eaghe GdGJUGdGJ (B: (3fXGe GdGJUGdGJ (B: (3GdJQhjL(B-(3GdaUd GdYGTQ (B: (3GdebOeI (B: (3CHYGO eaghe GdSYGQ hCgejJg (B: (3JYQja GdSYQ hGdJSYjQs
(3HjHdjhZQGajG U(B.345 , (3edGMb hCTcGd U(B. 355s
Keywords: (3GdUMIs; (3GdeSJTajGJs